GROUP PARTICIPATION IN INTEGRATED PEST CONTROL THROUGH THE ULTILIZATION OF TRICHOGRAMMA SP IN RICE BUSINESS IN SAMARANG DISTRICT, GARUT REGENCY: PARTISIPASI KELOMPOKTANI TERHADAP PENGENDALIAN HAMA TERPADU MELALUI PEMANFAATAN Trichogramma sp PADA USAHATANI PADI DI KECAMATAN SAMARANG KABUPATEN GARUT - Ummi Mahrani Nasution; Wida Pradiana; Wahyu Trisnasari (Jurnal Penyuluhan Pertanian, 2022)
One way to reduce the negative impact of pesticide use on rice plants is to carry out integrated pest control. As for pest control efforts that can be done is to utilize physical plant-disturbing organisms, namely natural enemies. This study was conducted to determine the level of farmer group participation in integrated pest control through the use of Trichogramma sp in rice farming, analyze the characteristics, external factors and IPM principles on the level of group participation in integrated pest control through the use of Trichogramma sp in rice plants and develop an extension strategy to increase participation. farmers. Based on the results of research from 68 respondents that the participation rate of farmer groups at the planning stage was 51.5% (medium), the implementation stage was 64.7% (medium) at the evaluation stage was 63.2% (medium). Factors that partially influence participation are length of farming (0.021), institutional role (0.032), social and cultural environment (0.000), utilization of natural enemies (0.001), routine monitoring (0.000), and farmers as IPM experts ( 0.037). Based on the high value beta coefficient taken from indicators that have a significant effect on the participation variable, a strategy is formulated to increase farmer group participation through strengthening the social and cultural environment, strengthening the frequency of monitoring land and plants so that farmers know the conditions and needs of these plants.